THE EFFECT OF ENTREPRENEURSHIP KNOWLEDGE ON SELF EFFICACY AND ITS IMPACT ON STUDENTS 'INTERESTS - Rindi Andriani; Nizar Alam Hamdani; Rahyuniati Setiawan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to determine the effect of Entrepreneurship Knowledge on Self Efficacy and its impact on entrepreneurial interest in students. This research uses descriptive and associative methods conducted on 68 respondents who are students of the, University of Garut. Data processing techniques used by researchers are validity, reliability, and data analysis methods using path analysis. The tool used is SPSS Software 20.0. The results of this study are entrepreneurial knowledge can affect self efficacy and have an impact on the emergence of entrepreneurial interest in students.